Assessment of cathodic protection effect on long‐distance gas transportation pipelines based on buried steel specimens. Issue 5 (23rd November 2020) - He, Guoxi; Peng, Hao; Liao, Kexi; Wang, Minan; Zhao, Shuai; Leng, Jihui
Abstract: Different severe corrosions are found at the damaged point of anticorrosive coating on natural gas pipelines, even though the cathodic protection (CP) potential is between −0.85 and −1.15 V. Therefore, there are totally 168 buried steel specimens (BSSs) and 28 soil samples at 28 buried points that are taken out in situ and then analyzed in the lab to assess the CP effectiveness. First, the CP status is simulated by BSSs at the damaged points,  and the corrosion products on BSSs are analyzed microscopically. Second, the corrosion rates of the testing BSSs are calculated by the weight‐loss method to perform the quantitative assessment. Third, the specific reasons for external corrosion are explored via analyzing the CP potential attenuation tendency and the corrosiveness of soil. The corrosion growth trend is also investigated by comparing the test results among three test cycles within 8 years. Finally, the control measures for external corrosion of pipelines are put forward. The study is beneficial to evaluate the CP system and determine the causes of external corrosion of pipelines, thereby formulating corresponding protective measures. Abstract : In total, 168 steel specimens at 28 buried points along the Sichuan‐to‐East gas pipeline were sampled and tested in situ. The tested mileage was up to 1120 km, where the cathodic protection effect of the steel specimens in three test cycles (with intervals of 1, 2, and 5 years, respectively) was evaluated, and the causes of external corrosion of the pipeline and protective measures were discussed.